Control of Inflammation by Calorie Restriction Mimetics: On the Crossroad of Autophagy and Mitochondria - Gabandé-Rodríguez, Enrique (Cells, 2019)
Mitochondrial metabolism and autophagy are two of the most metabolically active cellular processes, playing a crucial role in regulating organism longevity. In fact, both mitochondrial dysfunction or autophagy decline compromise cellular homeostasis and induce inflammation. Calorie restriction (CR) is the oldest strategy known to promote healthspan, and a plethora of CR mimetics have been used to emulate its beneficial effects. Herein, we discuss how CR and CR mimetics, by modulating mitochondrial metabolism or autophagic flux, prevent inflammatory processes, protect the intestinal barrier function, and dampen both inflammaging and neuroinflammation. We outline the effects of some compounds classically known as modulators of autophagy and mitochondrial function, such as NAD(+) precursors, metformin, spermidine, rapamycin, and resveratrol, on the control of the inflammatory cascade and how these anti-inflammatory properties could be involved in their ability to increase resilience to age-associated diseases.